Water and biogeochemical fluxes in the river Rhine catchment - Kempe, Stephan; Krahe, Peter (ERDKUNDE, 2005)
By combining measured precipitation and climatic data as well as observed discharge data with a conceptual hydrological model the water balance components for the time period 1961–1990 are calculated for selected sub-basins of the River Rhine. Based on this the water volumes and the various hydrological regimes, which are occurring in the River Rhine basin are discussed. An analysis of 100-year hydro-meteorological and hydrological time series have shown that changes arose in the past decades. Even if these regional changes cannot be assigned to anthropogenic induced climate changes with the highest statistical security in the mathematical sense, the assumption of stationarity of hydro-meteorological and hydrological time series is no longer valid. For the quantification of the effects of possible climate change on the discharge of the River Rhine and its tributaries extensive computations using regional climate scenarios for the entire River Rhine basin are necessary using water balance and/or river basin models. For these investigations three regional climate scenarios were available, which were provided in the context of project “Klimaveränderung und Konsequenzen für die Wasserwirtschaft” (KLIWA) for southern Germany. The climate scenario provided by the Max-Planck-Institute (MPI) for Meteorology in Hamburg, based on the regional climate model REMO, takes the entire River Rhine basin into account. This climate scenario is converted with the help of the hydrological models LARSIM and HBV-SMHI into discharges and the model results of selected gauges are analysed in view to the impact of possible climate change. The results are presented and their maximum stress is discussed. A short review of the biogeochemical fluxes estimated at selected measuring stations along the River Rhine is given. The described knowledge available on the biogeochemistry of the River Rhine illustrates the importance of understanding sources and processes of the biogeochemical important parameters in the River Rhine system.